Communication of the treasurer in relation to a loan to the Commonwealth : Treasury Office, December 28, 1842 (House document (Virginia. General Assembly. House of Delegates) ;, 1842)
December 8, 1842 communication from the Treasurer to the House of Delegates, regarding various banks' responses to the House resolution. Of note, the answers were not included in this document.